Utilization of Leaves in Mine Reclamation Land as Organic Fertilizer with Effective Bioactivatory of Microorganism 4 (em4) and Molasses - Supiana Dian Nurtjahyani; Dwi Oktafitria; Sriwulan Sriwulan; Nova Maulidina; Imas Cintamulya; Eko Purnomo (Indonesian Society for microbiology, 2020)
Organic fertilizer as an alternative to reduce the scarcity of chemical fertilizers, otherwise it can improve soil fertility. PT. Semen Gresik - Semen Indonesia Persero (Tbk.) Has a lot of plants in the treatment period in ex-mining land that needs fertilizer to help plant growth. In addition, in post-mining land, there is a lot of organic waste in the form of dry leaves under the stands of reclamation trees. The organic waste has the potential to be processed and used as organic fertilizer. This study aims to determine the utilize leaf litter in the reclaimed mine land as organic fertilizer with EM 4 and Molasses bioactivators. This study used is a laboratory experimental method. The results showed the composition of solid material in the form of leaf litter, bran, cow dung and husk charcoal in a ratio of 2: 1: 1: 1 as well as looking material in the form of molasses and EM4 with a dose of 100ml per 100kg of solid material dissolved in enough water (fertilizer can be clenched and expanded slowly and not broken). Conclusion leaf litter in the former reclaimed land can be processed and used as organic fertilizer.